Design and evaluation of conjugated polymers with polar side chains as electrode materials for electrochemical energy storage in aqueous electrolytes. Issue 4 (15th March 2019) - Moia, Davide; Giovannitti, Alexander; Szumska, Anna A.; Maria, Iuliana P.; Rezasoltani, Elham; Sachs, Michael; Schnurr, Martin; Barnes, Piers R. F.; McCulloch, Iain; Nelson, Jenny
Abstract : Solution processable p-type and n-type conjugated polymers with polar side chains enable fast charging in aqueous electrolytes and 1.4 V cell voltage. Abstract : We report the development of redox-active conjugated polymers that have potential applications in electrochemical energy storage. Side chain engineering enables processing of the polymer electrodes from solution, stability in aqueous electrolytes and efficient transport of ionic and electronic charge carriers. We synthesized a 3, 3′-dialkoxybithiophene homo-polymer (p-type polymer) with glycol side chains and prepared naphthalene-1, 4, 5, 8-tetracarboxylic-diimide-dialkoxybithiophene (NDI-gT2) copolymers (n-type polymer) with either a glycol or zwitterionic side chain on the NDI unit. For the latter, we developed a post-functionalization synthesis to attach the polar zwitterion side chains to the polymer backbone to avoid challenges of purifying polar intermediates. We demonstrate fast and reversible charging of solution processed electrodes for both the p- and n-type polymers in aqueous electrolytes, without using additives or porous scaffolds and for films up to micrometers thick. We apply spectroelectrochemistry as an in operando technique to probe the state of charge of the electrodes. This reveals that thin films of the p-type polymer and zwitterion n-type polymer can be charged reversibly with up to two electronic charges per repeat unit (bipolaron formation). We combine thin films of these polymers in a two-electrode cell and demonstrate output voltages of up to 1.4 V with high redox-stability. Our findings demonstrate the potential of functionalizing conjugated polymers with appropriate polar side chains to improve the accessible capacity, and to improve reversibility and rate capabilities of polymer electrodes in aqueous electrolytes.